Historical development of brain-language correlation - Donoso S., Archibaldo (Revista de Psicología, 1992)
The evolution of the concepts on the cerebral bases of oral language is reviewed, in the pre-scientific, scientific and contemporary periods. In the Pre-scientific Period, theoretical musings predominate, without an empirical basis, and in the Scientific Period innumerable clinical and antomo-clinical observations will accumulate. Currently, the biological substratum of language is seen as a functional system (in the sense of Luria), which has been corroborated by the progress of technology (computed tomography, etc.) and neurolinguistics.